Determinants of Long-Term versus Short-Term Bank Credit in EU Countries - Park, Haelim; Ruiz, Claudia; Tressel, Thierry (World Bank, Washington, DC, 2015)
This paper empirically examines the determinants of credit at different maturities across European Union countries during the last decade. The paper documents the lengthening of maturities since the early 2000s, and whether these patterns were driven by similar factors in advanced countries and in emerging market countries. Before the 2008 crisis, long-term credit expanded faster than short-term credit in most countries in the sample, and contracted less than short-term credit after 2008. The paper finds that domestic deposits and foreign liabilities were more important sources of funding in emerging market countries than in advanced countries. Moreover, trade openness and initial banking sector depth matter more for emerging market countries than for advanced countries.